Perancangan produk furnitur co-working space dengan konsep open space - Audi Firza Mulyana; Rahmawan Dwi Prasetya; Nor Jayadi (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2023)
Coworking Space is a place where individuals or groups have different work backgrounds in one place. In Indonesia, coworking spaces are developing, with proof of that is the emergence of coworking spaces in big cities, such as Jakarta, Bandung, Surabaya, and Yogyakarta. With the increasing demand, coworking spaces are currently experiencing development. One element that is quite close and plays an important role in work activities is a table and chairs. Various activities and various work backgrounds that gather in a limited space and spend quite a long time, demand a coworking space to be a versatile and comfortable place. Thus, we need furniture that can achieve effectiveness and still think about the concept of open space or sharing space with other users. This means that this furniture has more features, such as being able to be used individually or together. So that the designed tables and chairs can accommodate user needs and adjust the space that is expected to create comfort for working in a coworking space.